A Novel Power Saving Framework for Emissive Displays Using Contrast Enhancement Based On Histogram Equalization (International Journal of Engineering and Computer Science, 2014)
This paper proposes a novel power-constrained contrast-enhancement framework for emissive displays based on histogram equalization (HE).  To deduce the impact of the overstretching artifacts of the old HE log-based histogram is applied. Power-consumption model is developed for emissive displays and formulate an objective function that contain power term and histogram-equalizing term. The Proposed Framework provides contrast improve and power saving. Proposed algorithm is extend to improve the video sequences, as well as still images contrast and perceptual quality assessment..